Transcatheter Bariatric Embolotherapy for Weight Reduction in Obesity - Reddy, Vivek Y; Neužil, Petr; Musikantow, Daniel; Sramkova, Petra; Rosen, Robert; Kipshidze, Nicholas; Kipshidze, Nodar; Fried, Martin (Journal of the American College of Cardiology, 2020)
BACKGROUND: Obesity is well-appreciated to result in poor cardiovascular and metabolic outcomes. Dietary and medical weight loss strategies are frequently unsuccessful and unsustainable. Bariatric surgery is quite effective, but is reserved for the most obese patients because of the associated intraoperative/post-operative risks. In preclinical and early clinical case series, a novel therapy, transcatheter bariatric embolotherapy (TBE) of the left gastric artery, has been reported to promote weight loss by reducing ghrelin, an appetite-stimulating hormone secreted from the gastric fundus. OBJECTIVES: The purpose of this study was to examine TBE in a single-blind, sham procedure randomized trial. METHODS: Obese subjects (body mass index 35 to 55 kg/m2) were randomized 1:1 to either sham or TBE targeting the left gastric artery using an occlusion balloon microcatheter to administer 300- to 500-μm embolic beads. All patients entered a lifestyle counseling program. Patients and physicians performing follow-up were blind to the allocated therapy. Endoscopy was performed at baseline and 1-week post-procedure. The primary endpoint was 6-month total body weight loss (TBWL). RESULTS: Eligible subjects (n = 44; age 45.5 ± 9.4 years; 8 men/36 women; body mass index 39.6 ± 3.8 kg/m2) were randomized to undergo the sham or TBE procedure with no device-related complications and 1 vascular complication. Patients reported mild nausea and vomiting, and endoscopy revealed only minor self-limiting ulcers in 5 patients. At 6 months, in both the intention-to-treat and per-protocol populations, the TBWL was greater with TBE (7.4 kg/6.4% and 9.4 kg/8.3% loss, respectively) than sham (3.0 kg/2.8% and 1.9 kg/1.8%, respectively; p = 0.034/0.052 and p = 0.0002/0.0011, respectively). The TBWL was maintained with TBE at 12 months (intention-to-treat 7.8 kg/6.5% loss, per-protocol 9.3 kg/9.3% loss; p = 0.0011/0.0008, p = 0.0005/0.0005, respectively). CONCLUSIONS: In this randomized pilot trial, we have established the proof-of-principle that transcatheter bariatric embolotherapy of the left gastric artery is well-tolerated and promotes clinically significant weight loss over a sham procedure.(The Lowering Weight in Severe Obesity by Embolization of the Gastric Artery Trial [LOSEIT]; NCT03185949).
Keywords: Humans; ghrelin; lidé; Ghrelin; hypertenze; Obesity; hlad; Hypertension; kvalita života; gastrická arterie; odpověď na uspokojení; Female; lidé středního věku; terapeutická embolizace; Male; Adult; Embolization, Therapeutic; Hunger; dospělí; Quality of Life; Gastric Artery; Middle Aged; ženské pohlaví; mužské pohlaví; obezita; Satiety Response